2009
DOI: 10.1007/s10495-009-0397-8
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of doxorubicin to cell penetrating peptides sensitizes human breast MDA-MB 231 cancer cells to endogenous TRAIL-induced apoptosis

Abstract: Previous work from our laboratory has shown that coupling doxorubicin (Dox) to cell penetrating peptides (Dox-CPPs) is a good strategy to overcome Dox resistance in MDA-MB 231 breast cancer cells. We also reported that, in contrast to unconjugated Dox-induced cell death, the increase in apoptotic response does not involve the mitochondrial apoptotic pathway. In this study, we demonstrate that both Dox and Dox-CPPs can increase the density of the TRAIL receptors DR4 and DR5 at the plasma membrane and moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Interestingly, removing the last 8 C-terminal amino acids of MCa had little impact on the cell penetration properties (if one compares MCa UF14 -25 -C with MCa UF14 -33 -C). Similarly, the removal of the amino acid region His 6 -Asn 13 did not drastically change cell penetration properties (MCa UF6 -25 -C versus MCa UF14 -25 -C). Second, all peptides appeared to behave better than the reference peptide MCa UF1-33 -C, suggesting that sequence truncation of MCa UF may represent a potent strategy to define more efficient CPPs.…”
Section: Nonfolded Truncated Maurocalcine Peptides Are Efficient Cpps-mentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, removing the last 8 C-terminal amino acids of MCa had little impact on the cell penetration properties (if one compares MCa UF14 -25 -C with MCa UF14 -33 -C). Similarly, the removal of the amino acid region His 6 -Asn 13 did not drastically change cell penetration properties (MCa UF6 -25 -C versus MCa UF14 -25 -C). Second, all peptides appeared to behave better than the reference peptide MCa UF1-33 -C, suggesting that sequence truncation of MCa UF may represent a potent strategy to define more efficient CPPs.…”
Section: Nonfolded Truncated Maurocalcine Peptides Are Efficient Cpps-mentioning
confidence: 83%
“…Studies that were undertaken to demonstrate the ability of MCa to reach its target showed that (i) MCa triggers Ca 2ϩ release from the SR a few seconds after its application in the extracellular medium (5) and (ii) intracellular accumulation of fluorescent-streptavidin occurs if it incubated first with biotinylated MCa (10). Since these pioneering studies, MCa or analogues thereof proved powerful vectors for the cell entry of proteins, peptides (11), nanoparticles, or drugs such as doxorubicin (12)(13)(14)(15). Although the mode of cell penetration of MCa may vary according to cargo nature, cell type, or chemical linkage employed, the data gathered so far suggest that the peptide may enter cells according to two priming steps onto the plasma membrane: first an interaction with proteoglycans with an affinity in the micromolar range, followed by a second interaction with negatively charged lipids which occurs with greater affinity (16,17).…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%
“…Efficient induction of apoptosis by CPP-DOX was found in the human breast cancer cell line MDA-MB-231. 8,9 In addition, various CPPdrug conjugates have also been developed to improve antitumor efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…our recent study showed that oxaliplatin enhances Trail sensitivity by clustering death receptors into lipid rafts (7). aroui et al reported that doxorubicin sensitizes breast cancer cells to Trail by triggering lipid raft aggregation (17). doxorubicin and epirubicin are both anthracyclines, but whether epirubicin is capable of regulating lipid rafts and thus enhancing the sensitivity of gastric cancer cells to Trail remains to be determined.…”
Section: Introductionmentioning
confidence: 99%